Systematic review of empirical studies on citizenship education in Latin America 2000 to 2017 and research agenda proposal. (August 2020) - Bramwell, Daniela
This article will be of interest to anyone wishing to conduct research related to citizenship education in Latin America. It shares the results of a systematic review of empirical studies with the goal of (a) mapping the current research on citizenship education in Latin America and (b) suggesting a research agenda for citizenship education in Latin America. One particular contribution of this article is that it describes research that was previously accessible only to those who read Spanish. Findings include an increase in publications on citizenship education in Latin America since 2000 and show that research is being published on (1) the content of official documents, (2) what happens in educational settings, (3) teachers' views, (4) students' views, (5) what influences students' civic outcomes and (6) students' civic identities. The final section of the article explores various suggestions for future research.